Environmental Cost Efficiency Analysis to Improve the Quality of Waste Management from an Economic Perspective - Camila Adistyawati (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
Evironmental cost holds an important role in minimizing waste disposal which is produced by manufacturing company. Eco Profit Ratio is used to see whether the costs being spent have already been efficient from economic perspective in waste management process to minimize pollution. This research is prepared by explaining the use of Eco Profit Ratio in order to know how large the efficiency from economic perspective of environmental costs. This research studies a case of CV Kokidi Sejahtera Printing in seven semester from 2017 to 2020 using a descriptive qualitative method. The ratio which used in this research is based on formula from Hansen and Mowen, by dividing the environmental profit with environmental conservation cost that the company has spent for waste management processing. The result of this research showed that the environmental cost of the company are classified as prevention cost. Meanwhile the eco profit ratio showed an inefficiency of the environmental cost that has been spent, in which the value is under zero.